Collagen and Hydroxyapatite Scaffolds Activate Distinct Osteogenesis Signaling Pathways in Adult Adipose-Derived Multipotent Stromal Cells - Duan, Wei (Tissue Eng Part C Methods, 2017)
Osteogenic cell signaling pathway disruption varies among bone diseases. This investigation was designed to identify adipose-derived multipotent stromal cell (ASC) and bone graft scaffold combinations for local, targeted restoration of gene expression and extracellular matrix (ECM) deposition. Human ASC osteogenesis on bone graft materials was quantified following culture in stromal (S), osteogenic (O), or osteogenic for 48 h followed by stromal medium (OS) to test the two-part hypothesis: (1) identical ASC isolates on distinct bone graft scaffolds demonstrate unique viability, differentiation, ECM production, and gene expression in the same culture conditions; (2) identical ASC-bone graft scaffold combinations have different cell viability, differentiation, ECM production, and gene expression when cultured in S, O, or OS medium. Three commercially available bone graft scaffold materials, type I bovine collagen (C), hydroxyapatite + β-tricalcium phosphate + type I bovine collagen (HT), and β-tricalcium phosphate + type I bovine collagen (CT) were evaluated. Passage 3 ASCs were loaded onto scaffold blocks with a spinner flask bioreactor, and constructs were cultured up to 28 days. Cell viability, gene expression (alkaline phosphatase [ALPL], osteoprotegerin [TNFRSF11B], osteocalcin [BGLAP], cannabinoid receptors type I [CNR1] and II [CNR2], receptor activator of nuclear factor kappa β ligand [TNFSF11]), as well as ECM DNA, collagen, sulfated glycosaminoglycan, and protein content were quantified. Matrix organization was evaluated with scanning electron microscopy. Effects of scaffold, medium, or culture duration on cell viability were minimal. Significantly higher initial ALPL expression decreased with time, while BGLAP expression increased in HT constructs in O medium, and the constructs had the most abundant ECM components and ultrastructural organization. There was a similar, although delayed, pattern of gene expression and greater ECM collagen with less organization in C constructs in O medium. Higher CNR1 expression in C versus higher TNFRSF11B/TNFSF11 expression in HT constructs throughout the study support stimulation of unique osteogenic signaling pathways by identical cell isolates. These results suggest that bone scaffold composition may be used to selectively target specific osteogenic cell signaling pathways in ASC constructs to stimulate ECM deposition based on therapeutic needs.